Functional Mitral Regurgitation in Patients with Preserved Ejection Fraction Qualified for Pulmonary Vein Isolation: A Negative Prognostic Factor for Catheter Ablation Efficacy - Małgorzata Cichoń; Maciej Wybraniec; Magdalena Mizia-Szubryt; Katarzyna Mizia-Stec (Medicina, 2021)
Background and Objectives: Functional mitral regurgitation (F-MR) observed in patients with atrial fibrillation could affect the effectiveness of the sinus rhythm restoring procedures. The aim of the study was to evaluate the impact of F-MR on pulmonary vein isolation (PVI) efficacy in patient with preserved ejection fraction (EF). Materials and Methods: One hundred and thirty-six patients with EF ≥ 50% (65.4% males; mean age 56 ± 11 years) with symptomatic paroxysmal or persistent AF qualified for PVI were enrolled into the study. F-MR assessment was performed in transthoracic (TTE) and transesophageal (TEE) echocardiography before the PVI procedure. PVI efficacy was evaluated in three-month and long-term follow-up. Results: F-MR was diagnosed in 74.3% patient in transthoracic echocardiography (TTE) (trace: 26.5%, mild: 43.4%, moderate: 3.7%, severe 0.7%) and 94.9% in transesophageal echocardiography (TEE) (trace: 17.6%, mild: 59.6%, moderate: 16.2%, severe: 1.5%). The PVI three-month efficacy was 75.7% in the three-month and 64% in the long-term observation. Severe F-MR in TEE at baseline was associated with lower three-month PVI efficacy (p = 0.012), while moderate to severe F-MR in TEE was related to inefficient PVI assessed in long-term follow-up (p = 0.041). Conclusions: Significant F-MR confirmed by TEE predicts three-month as well as long-term PVI efficacy.